The Implementation of the Historical Memory Law in the City of Corunna (2021)
The following article presents an exploratory study about the implementation in a middle-sized city of the so-called Historical Memory Law (established in 2007). Through heraldry and numismatics, considering the evolution of the coats of arms of Spain (2nd Republic, Francoism and constitutional monarchy), it was analyzed Francoism symbolism and the execution of the law in the city of Corunna based on a documentary analysis of the city council acts in 2007-2019 lapse. The main conclusion was that the practical implementation of this legal code, apart from being based on symbols of ambiguous cataloging, varied significantly based on the ruling party at the moment (Partido Socialista Obrero Español, Partido Popular y Marea Atlántica); making clear that way that the political parameters prevailed over history and law. © 2021 FahrenHouse. All rights reserved.